The mechanical properties of toughened poly(methyl methacrylate) sheet materials (part 1) - Mohd Yusof, Zainal Abidin; Hashim, Shahrir; Rahmat, Abdul Razak (Faculty of Chemical & Natural Resources Engineering, 1994)
The project was concerned with structure-property relations toughened grades of poly(methyl methacrylate), PMMA sheet with various weight fractions of rubber particles. The deformation and fracture behaviour of rubber toughened PMMA cast sheet materials have been studied using tensile testing. There were found that the Young's modulus, yield stress and ultimate tensile strength of the rubber-toughened PMMA materials decreased as weight fraction of the rubbery phase increase, but nevertheless the ultimate strain increases with an increase in the percentage rubber particle.